N-Carbamoylglutamate Supplementation on the Digestibility, Rumen Fermentation, Milk Quality, Antioxidant Parameters, and Metabolites of Jersey Cattle in High-Altitude Areas - Liu, Zixin; Yan, Fuyong; Mi, Hui; Lv, Xiaokang; Wang, Kaijun; Li, Bin; Jin, Tao; Chen, Liang; Zhang, Guijie; Huang, Ximei; Zhou, Chuanshe; Tan, Zhiliang (Frontiers in Veterinary Science, 2022)
This study aimed to assess the impact of the dietary supplementation of N-carbamoylglutamate (NCG) on nutrients digestibility, rumen fermentation, milk quality, oxidative stress, and metabolites in plasma of Jersey cattle under high altitude with the hypoxic condition. A total of 14 healthy lactating Jersey dairy cows with similar body conditions were selected and randomly divided into 2 groups, each with 8 heads. The control group (CON group, N = 6 replicates) was fed with a conventional complete diet, whereas the experimental group (NCG group, N = 8 replicates) received 20 (g/d·head) NCG supplementation. The experiment lasted for 60 days, the adaptation period was 12 days, and the formal experiment period was 48 days. Except that the NCG group showed an upward trend in OM digestibility (P = 0.09), the two groups had no significant differences (P＞0.05) in nutrients digestibility, fermentation parameters, plasma immunity and antioxidant ability. But compared with the CON group, the milk fat rate and blood oxygen saturation of the NCG group showed an upward trend (P = 0.09). For indexes associated with altitude stress, the contents of thyroxine and endothelin both decreased significantly (P<0.05) in the NCG group. Meanwhile, heat shock protein (P=0.07), aldosterone (P=0.06) and transferrin (P=0.06) were also showed a downward trend. A total of 114 different metabolites were identified from feces and plasma, 42 metabolites were derived from plasma, mainly including Lipids and lipid-like molecules, Benzenoids, Organic acids and derivatives and other 2 kinds of Super Class, and 72 metabolites were derived from feces, mainly including Lipids and lipid-like molecules, Organoheterocyclic compounds, Phenylpropanoids and polyketides and other 6 kinds of Super Class. Pathway analysis showed that after applying NCG as a feed additive, the changes of the Jersey dairy cows mainly focused on amino acid metabolism and lipid metabolism. These results indicated that adding NCG to the diet can prevent the hypoxic stress state of lactating Jersey cows in high altitude areas and has a tendency to improve milk quality.